Lamellar congenital ichthyosis in practice of dermatologists - S. V. Koshkin; T. V. Chermnykh; A. L. Evseeva; V. V. Ryabova; A. N. Ryabov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The paper describes 2 cases of congenital lamellar ichthyosis debuting state «collodion baby». Presented features of clinical manifestations: in newborn all skin is covered with a thin dry yellowish-brown film, resembling collodion, also ectropion and eklabium are frequently marked. After some time cracks appear, the film turns into large squamas, which exfoliate completely in 1.5 months, and so the clinical picture of congenital ichthyosis is formed. Timely initiated therapy, including external moisturizers and lipid-replenishing funds, contributed to the rapid relief of clinical symptoms and infectious-inflammatory process.